An Effect of Accounting on Tax Avoidance Food and Beverage Sub Sector Manufacturing Companies Listed Indonesia Stock Exchange (IDX) - Reny Maisyarah (Budapest International Research and Critics University, 2022)
This study aims to identify the effect of accounting conservatism, audit committee, independent board of commissioners, institutional ownership, and firm size on tax avoidance in the Manufacturing Industry of the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange. Tax avoidance is the dependent variable in this research, measured by the Effective Tax Rate. The independent variables studied were accounting conservatism, audit committee, and independent board of commissioners. The information used was obtained from financial reports and annual reports published via webwww.idnfinancials.com. Information analysis used in this research is the associative method. The illustration method used is purposive sampling with a total sample of 5 companies and information from 2016-2020. The results of this research show that the audit committee has a significant positive effect on tax avoidance. On the other hand, accounting conservatism has a significant negative impact, and the independent board of commissioners does not have a significant positive effect on tax avoidance.